Assessing the Impact of Ground Control Point (GCP) on the Output of UAV Photogrammetry Image - Mohamad Zaki, Muhammad Syazwi; Daud, Mohd Effendi; Siddiq, Mohammad Ikhmal; Kaamin, Masiri (Recent Trends in Civil Engineering and Built Environment, 2024)
In this modern era, in order to get an excellent mapping and high accuracy data, fundamentally by unmanned aerial vehicle. Unmanned aerial vehicle (UAV) photogrammetry has lately developed as a preferred method for obtaining high accuracy outputs with aid of Ground Control Point (GCP) required in linear mapping, such as Orthomosaic, Digital Surface Models (DSM), and Digital Terrain Models (DTM). For this, there are several fundamental issues to consider, such as what was the need for GCP in mapping while Non-GCP could also contribute data, whether UAV photogrammetry without GCP is capable or not of being applied in all types of civil engineering work, the advantages of GCP and Non-GCP output in mapping, and the importance of GCP and Non-GCP data output accuracy in Civil Engineering. The aimed of this study is to assessing the impact of Ground Control Point (GCP) output by using UAV Photogrammetry method in order to find out the accuracy effectiveness in mapping that could contribute in civil engineering field which were by comparing with Non-GCP data from the changes of shoreline, height of contour, coordinate, volume and cross section area. A DJI Phantom 4 Pro with assist RTK GNSS receiver was used to synchronous with the GPS to allocate the GCP position along 1kmx100m along Pantai Punggur, Batu Pahat. There are 14 GCP along the shoreline. The images were captured by the UAV in setting up the route in Pix4D Capture with the 80 percent front overlap, 60 percent side overlap and 50m of latitude in 30 minutes of fly duration in two month which is once a month. Thus, there are four orthomosaic which were two with GCP and two without GCP. From the data analyze, there were relative and absolute errors. The mean RMSE for Mac GCP was 0.008m while May GCP was 0.006m. The Non-GCP image does not contain any RMS error as the data does not contain any prior marking in the initial processing. From the data analysis, there was a big error from an absolute error for contour elevation, shoreline, coordinate and orientation of the orthomosaic, And, the small error from a relative error for volume and distance point to point of the GCP. In conclusion for the accuracy work in civil engineering it reserved which was need to use the GCP while the Non-GCP can be used for something that does not require high accuracy such as obtaining a visual of a study area in general, an initial overview of a study and monitoring work.